Stratigraphy and correlation of the Late Wisconsinan glacial events in the Lake Michigan basin - Evenson, E.; Mickelson, D.; Farrand, W. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
Meaningful correlations of late glacial events between areas as distant as the Great Lakes and southern Quebec depend on the establishment of detailed local chronologies, mostly from studies in the Lake Michigan basin and the St. Lawrence lowland now holding the most promise for a radiometrically controlled record of the late glacial (ca. 14,000-8000). Based on recent investigations in the Lake Michigan region, we propose a revision in the déglaciation pattern and stratigraphie nomenclature. Although oscillatory glacial retreat began to dominate over readvance about 17,000 years BP, we define late Wisconsinan as beginning at ca. 14,000 when the ice withdrew from the Lake Border Morainic system. Following the Cary-Port Huron retreat, the ice read-vanced (350 km) depositing the red Shorewood Till. This was followed by a minor retreat and then by deposition of the Manitowoc Till. Continued retreat eventually uncovered an eastward outlet and Lake Chicago dropped to the Two Creeks low-water level. This déglaciation was not as extensive as previously assumed. The post-Twocreekan readvance (125 km) to the Two Rivers moraine oc-cured around 11,850 years BP. This sequence argues for a normal, climatically controlled progressive déglaciation rather than one interrupted by a major post-Twocreekan (formally Valderan) surge. Based on the knowledge that the Valders Till is late Woodfordian in age we have proposed the time-stratigraphic term "Greatlakean" as a substitute for the now misleading term "Valderan".